Design Of Environmental Conditions Of Transportation Simulation Instruments On Tomato (Solanum Lycopersicum) - Mufidah, Zunanik; Jordy, Abdul Rachman; Fil'aini, Raizummi; Telaumbanua, Mareli; Fatikhunnada, Alvin (Universitas Brawijaya, 2023)
Based on data from Badan Pusat Statistik (BPS) in 2017-2018, the tomato productivity in Indonesia has seen a year-on-year increase of 10% and 19%. However, during the transportation process of agricultural commodities, excessive vibration can lead to damage of tomato commodities. Therefore, the purpose of this study is to develop an environmental data recording device using Arduino technology, and to assess its performance by simulating vibration during transport. The aim is to ensure proper handling and storage of tomato commodities in the distribution process. The designs used are programming designs, functional designs, and structural designs. The results showed that the design of an arduino-based environmental data recording instrument, calibration results between the DHT22 sensor (temperature) and a digital hygrometer yielded a correlation equation value of y = 1.0475x – 1.5575, R2 for the DHT22 sensor was 0.9885, and for the calibration results between the vibration sensor and the vibrating table as a calibrator obtained a correlation equation value of y = 1.9471x-101.24, the calibration R2 value was 0.8088, the instrument accuracy performance test results were obtained by 80%. The stability test results of reading past the setting point, the control speed is 4.04 minutes, the result of the reliability coefficient value (r11) is 0.90. The reliability coefficient value from the stability test results is included in the very high reliability category, the system response at a setting point of 150 RPM takes 63 seconds and the system response at a setting point of 200 RPM takes 71 seconds. characteristics that occur in tomatoes during the transportation simulation process where at 100 RPM the test was carried out, the tomatoes experienced a collision and only a few were bruised due to the shock from the transportation simulation the tomatoes were damaged and collided between the tomatoes in the box, the greater the vibration received by the tomatoes on during the transportation simulation, the more tomatoes will experience physical damage.Test results on tomatoes with a degree of mechanical damage (bruises) due to vibration during transportation. In stack 1 100 RPM there was no damage to the fruit while the biggest bruising occurred in stack 3 with 200 RPM.